Affective Commitment of Public-School Principals : How do Organizational Justice and Job Satisfaction Affect the Commitment? - Hegar Harini; Adisel Adisel; Ahmad Jauhari Hamid Ripki; Herlina Herlina; Sulistianingsih Sulistianingsih (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This research aims to examine the effect of organizational commitment and job satisfaction on high school principals’ affective commitment. The research employed a quantitative survey. The samples researched were 90 senior high school principals in Jakarta. The data were collected through a series of questionnaires. The data were then analyzed using descriptive statistics and path analysis. The results indicated that: 1) organizational commitment gave a positive direct effect on the principals’ affective commitment; 2) job satisfaction gave a significant direct effect on the principals’ job satisfaction, and 3) organizational commitment gave a positive direct effect on the principals’ job satisfaction. The present research implies that the provincial education board is strongly suggested to keep performing fair procedural justice prescribed by regulations to maintain the principals working satisfactorily and feeling attached to their schools.